Vulnerable sandstone reefs: Biodiversity and habitat at risk - Soeth, Marcelo; Metri, Rafael; Simioni, Bruno Ivan; Loose, Robin; Coqueiro, Guilherme Suzano; Spach, Henry Louis; Daros, Felippe Alexandre [UNESP]; Adelir-Alves, Johnatas (Elsevier, 2020)
Sandstone reefs may be considered a unique geomorphologic feature within the subtropical Southwestern Atlantic Ocean region; however, biodiversity on these reefs has received little to no attention. Herein, we recorded the fish assemblage and benthic cover of sandstone reefs between 23 and 29 m depth in Southern Brazil and evidenced potential threats to habitat health. Video analysis and underwater censuses recorded 30 fish species. The unexpected high biomass of Epinephelus marginatus indicated that sandstone reefs may contain suitable habitats for the recovery of this endangered species. A rich benthic coverage including bryozoans, algae, hydrozoans, sponges, and octocorals increased local habitat structural complexity. However, a wide diversity of tangled fishing gear and broken sandstone slabs suggested that a valuable feature from Southern Brazil seascape is being lost by cumulative fishing impacts. An extensive mapping of sandstone reefs is urgently needed for better delineation of marine protected areas network in Southeast and Southern Brazil.
Keywords: Checklist; Fishing threats; Marine animal forest; Marine spatial planning; Reef fish